Comparative toxicological assessment of PAMAM and thiophosphoryl dendrimers using embryonic zebrafish - Pryor JB (Dove Medical Press, 2014)
Joseph B Pryor,1 Bryan J Harper,1 Stacey L Harper1,21Department of Environmental and Molecular Toxicology, Oregon State University, Corvallis, OR, USA; 2School of Chemical, Biological, and Environmental Engineering, Oregon State University, Corvallis, OR, USAAbstract: Dendrimers are well-defined, polymeric nanomaterials currently being investigated for biomedical applications such as medical imaging, gene therapy, and tissue targeted therapy. Initially, higher generation (size) dendrimers were of interest because of their drug carrying capacity. However, increased generation was associated with increased toxicity. The majority of studies exploring dendrimer toxicity have focused on a small range of materials using cell culture methods, with few studies investigating the toxicity across a wide range of materials in vivo. The objective of the present study was to investigate the role of surface charge and generation in dendrimer toxicity using embryonic zebrafish (Danio rerio) as a model vertebrate. Due to the generational and charge effects observed at the cellular level, higher generation cationic dendrimers were hypothesized to be more toxic than lower generation anionic or neutral dendrimers with the same core composition. Polyamidoamine (PAMAM) dendrimers elicited significant morbidity and mortality as generation was decreased. No significant adverse effects were observed from the suite of thiophosphoryl dendrimers studied. Exposure to ≥50 ppm cationic PAMAM dendrimers G3-amine, G4-amine, G5-amine, and G6-amine caused 100% mortality by 24 hours post-fertilization. Cationic PAMAM G6-amine at 250 ppm was found to be statistically more toxic than both neutral PAMAM G6-amidoethanol and anionic PAMAM G6-succinamic acid at the same concentration. The toxicity observed within the suite of varying dendrimers provides evidence that surface charge may be the best indicator of dendrimer toxicity. Dendrimer class and generation are other potential contributors to the toxicity of dendrimers. Further studies are required to better understand the relative role each plays in driving the toxicity of dendrimers. To the best of our knowledge, this is the first in vivo study to address such a broad range of dendrimers.Keywords: nanomaterials, in vivo, toxicity, generation, surface chemistry, zebrafish